2006
DOI: 10.3136/fstr.12.247
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Arachidonoyl Glycerols Encapsulated with Saccharides

Abstract: Two types of lipids rich in arachidonic acid content were encapsulated using various saccharides as the wall material, and the oxidation processes of the encapsulated lipids were measured at /*ῌ and +,ῌ relative humidity. One of the lipids contained arachidonoyl residue at a content of ca. .*ῌ, and another was a structured lipid, the major component of which was +,--octanoyl-,-arachidonoyl glycerol. Microencapsulation e#ectively retarded their oxidation. In particular, among the tested saccharides, soluble soy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Oil microencapsulation consists of two steps: the first is the homogenization of oil or lipid with a dense solution of wall material to produce the O/W emulsion, followed by the rapid dehydration of the resultant O/W emulsion to yield microcapsules. Encapsulation of oil can suppress or retard the oxidation, 55,56) the extent of which depends on the kind of wall material, 57,58) ratio of core material (oil) to wall material, 59,60) drying method and its conditions, 61,62) and storage conditions of microcapsules. 63) Since the exposed oil on the surface of the microcapsule is prone to oxidation, the surface oil content, which is defined as the ratio of the amount of oil exposed on the microcapsule surface to the whole oil in the microcapsule, would be related to the susceptibility of microencapsulated oil to autoxidation.…”
Section: VI Factors Affecting Autoxidation Of Microencapsulated Oilmentioning
confidence: 99%
“…Oil microencapsulation consists of two steps: the first is the homogenization of oil or lipid with a dense solution of wall material to produce the O/W emulsion, followed by the rapid dehydration of the resultant O/W emulsion to yield microcapsules. Encapsulation of oil can suppress or retard the oxidation, 55,56) the extent of which depends on the kind of wall material, 57,58) ratio of core material (oil) to wall material, 59,60) drying method and its conditions, 61,62) and storage conditions of microcapsules. 63) Since the exposed oil on the surface of the microcapsule is prone to oxidation, the surface oil content, which is defined as the ratio of the amount of oil exposed on the microcapsule surface to the whole oil in the microcapsule, would be related to the susceptibility of microencapsulated oil to autoxidation.…”
Section: VI Factors Affecting Autoxidation Of Microencapsulated Oilmentioning
confidence: 99%
“…60) Another study encapsulated two types of lipids rich in arachidonic acid in various saccharides, in which soluble soybean polysaccharide (SSPS) and gum arabic showed the best oxidation suppression. 61) SSPS microencapsulation was also effective at suppressing linoleic acid. 62) Further research fractionated SSPS into its low and high molecular weight components to examine their respective antioxidative and emulsifying properties and indicated that the low molecular weight component in particular was responsible for the oxidative suppression of linoleic acid observed in the previous study.…”
Section: Oxidation Of Microencapsulated Lipidsmentioning
confidence: 95%
“…Encapsulation of SLs is a new issue of scientific studies hence there are only two studies in the literature that considered microencapsulation of SLs via spray drying technology (Kikuchi et al, ; Nagachinta & Akoh, ). From this point, our study will be unique since it is aimed to encapsulate MLM‐type SLs by complex coacervation technology.…”
Section: Introductionmentioning
confidence: 99%